Geographical Variations of Disorders of Sex Development (DSD) in South Sumatera Region - Ziske Maritska; Bintang Arroyantri Prananjaya; Zabila Adwie Prilishia; Nita Parisa; Sativandi Riza (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
ABSTRACT Background. Disorders of Sex Development (DSD) is a condition where the development of sex chromosomes, gonads, and/or one’s anatomy is atypical. Its causes are often due to genetic mutations, although some are also linked to environmental risk factors. These multiple aetiologies lead to varied clinical findings, ranging from obvious ambiguous genitals to subtle ones in different regions worldwide, signalling a hint of geographical variability. Objective. This study wishes to observe the variations of clinical findings of DSD patients geographically in South Sumatera. Methods. This was an observational study using patients’ medical records in RSUP Dr. Mohammad Hoesin Palembang. Both inpatients and outpatients during five-year period span (2013-2017) with clinical findings suited DSD criteria based on Chicago Consensus in 2006 were included in this study. Results. One hundred and forty nine patients from cities and regencies in South Sumatera province and other provinces like Jambi, Lampung, Bengkulu, Bangka-Belitung, and even Riau were included in this study. Among sixteen clinical findings identified, hypospadias ranked first (59.06%), both in general, and in each regions as well. When set by side with other regions, Palembang city as the capital city of South Sumatera province displays twelve out of sixteen clinical findings documented in this study, showing a lot more variety. Conclusion. Every regions show difference clinical findings. Some regions housed clinical findings that were not found in other regions. However, hypospadias is the most commonly found clinical findings in all regions. It is suspected due to its correlation with certain environmental risks, that the occurence of it becomes rather often, compared to other DSD conditions. Future studies considering risk factors involvement in order to elucidate both differences and similarities found in each regions are strongly suggested. Keywords: Disorders of Sex Development, DSD, Geographical variations, South Sumatera